Gambaran Tingkat Pengetahuan Ibu Tentang Karies Pada Gigi Anak Usia 3-5 Tahun di Klinik Aesthetic Dental Care - Annisa, Nurul; Qalbi, Astri Annur; Sadam, Muhammad (Barongko: Jurnal Ilmu Kesehatan, 2025)
The problem in this study is the lack of maternal knowledge about caries in the teeth of children aged 3-5 years at the Aesthetic Dental Care clinic. The purpose of this study is to find out the extent of maternal knowledge about caries in the teeth of children aged 3-5 years at the Aesthetic Dental Care clinic. The method in this study is that the research design used is a descriptive design. The sampling technique used was consecutive sampling with a direct examination method, with a sample of 30 respondents and by filling out a questionnaire sheet. The research data analysis technique is to calculate the average answer based on the scoring of each answer from the respondents. The total number of answersobtained from the respondents, is calculated in the form of distribution, frequency and percentage and presented in the form of a table. The resultsof this study are the Level of Maternal Knowledge about Caries in Children Aged 3-5 Years at the Aesthetic Dental Care Clinic shows that the majorityof mothers have good knowledge about caries which is 56.7%. Meanwhile, 30% of mothers have sufficient knowledge and 13.3% have less knowledge. The average respondent in this study showed that as many as 75% of mothers were able to answer correctly about dental caries. This shows that the majority of mothers have a good knowledge of caries, thus affecting mothers' attitudes and actions in maintaining children's dental and oral health.